2017
DOI: 10.1111/jopy.12334
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal feedback between self‐concept and goal pursuit in daily life

Abstract: The results are the first to indicate the existence of reinforcing feedback loops between self-concept clarity and grit, such that fluctuations in the clarity of self-knowledge are associated with fluctuations in goal resolve, and vice versa. Discussion centers on the implications of these results for the functional link between mind and action and on the study's heuristic value for subsequent research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…In Emily’s case, the transferability of skills from the MA TESOL programme provided her with the tools to achieve her future self. This finding is consistent with Wong and Vallacher (2018) who maintained that the way a person defines himself provides a frame of reference for sustained action in pursuing their personal goals. However, in this study, self-knowledge and goal pursuit appear to also be mutually reinforcing.…”
Section: Discussionsupporting
confidence: 89%
“…In Emily’s case, the transferability of skills from the MA TESOL programme provided her with the tools to achieve her future self. This finding is consistent with Wong and Vallacher (2018) who maintained that the way a person defines himself provides a frame of reference for sustained action in pursuing their personal goals. However, in this study, self-knowledge and goal pursuit appear to also be mutually reinforcing.…”
Section: Discussionsupporting
confidence: 89%
“…Especially in Study 2, grit was found to be functional in mediating the relationship between interpersonal stress and psychological security, which provides implications for future interventions of grit or psychological security. On the one hand, grit is not fixed to some extent, but relatively variable and plastic ( Wang et al, 2018 ; Alan et al, 2019 ), which could be affected by external or internal factors ( Wong and Vallacher, 2018 ); therefore, intervention methods can be used in the future. For example, improving academic performance ( Tang et al, 2019 ), expanding social support ( Wallace et al, 2001 ), and fostering growth mindset ( Wang et al, 2018 ) can improve the grit level of individuals ( Alan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, for example, that SCC state is influenced by the regularity of an individual's emotions and behaviors, while at the same time serving as a resource for further emotion and behavior regulation, as in a positive feedback loop. Recently, Wong and Vallacher (2017) investigated this general question using daily diary data and cross-lagged multilevel structural equation modeling. They found, on average, a reciprocal relationship between SCC and grit, such that SCC predicted grit two days later, and grit predicted SCC across the same interval.…”
Section: Introductionmentioning
confidence: 99%